A note on the pyjama problem - Malikiosis, R.D. (2013)
This note concerns the so-called pyjama problem, whether it is possible to cover the plane by finitely many rotations of vertical strips of half-width ε. We first prove that there exist no periodic coverings for ε<1/3. Then we describe an explicit (non-periodic) construction for ε=1/3 - 1/48. Finally, we use a compactness argument combined with some ideas from additive combinatorics to show that finite coverings exist for all ε>1/5. The question whether ε can be arbitrarily small remains open.